2017
DOI: 10.1039/c7cp05124g
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the forbidden regions of the Ramachandran plot (ϕ-ψ) with QTAIM

Abstract: A new QTAIM interpretation of the Ramachandran plot is formulated from the most and least facile eigenvectors of the second-derivative matrix of the electron density with a set of 29 magainin-2 peptide conformers. The presence of QTAIM eigenvectors associated with the most and least preferred directions of electronic charge density explained the role of hydrogen bonding, HH contacts and the glycine amino acid monomer in peptide folding. The highest degree of occupation of the QTAIM interpreted Ramachandran plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…This promises better-than-force field accuracy as well as access to some electronic properties including electron density itself, which allow performing analyses which are in principle impossible with force fields. 21,22 Linear-scaling KS-DFT approaches have been proposed [23][24][25] but remain costly (large prefactors) and introduce additional approximations. OF-DFT inherently can have near-linear scaling, but not all KEF models are linear-scaling.…”
Section: Introductionmentioning
confidence: 99%
“…This promises better-than-force field accuracy as well as access to some electronic properties including electron density itself, which allow performing analyses which are in principle impossible with force fields. 21,22 Linear-scaling KS-DFT approaches have been proposed [23][24][25] but remain costly (large prefactors) and introduce additional approximations. OF-DFT inherently can have near-linear scaling, but not all KEF models are linear-scaling.…”
Section: Introductionmentioning
confidence: 99%
“…Figure E shows that the 3D molecular structures of P361, P362, P371, and P372 were modeled via the I-TASSER server, and the LeuA-P domain and the lysin domain are colored red and green, respectively. The Ramachandran plot analysis (Figure S4) showed that more than 90% of the φ and ψ dihedral angles of the 3D models of the four new chimeric lysins were distributed in the allowable area and proved that the structures of molecular modeling were accurate . It can be seen from Figure F that P362, P371, and P372 retained the α-helical amphiphilic cationic peptide structure of LeuA-P, while the LeuA-P structure of P361 was changed and its helical structure was shifted to the N-terminal.…”
Section: Resultsmentioning
confidence: 95%
“…The constructed structural models were analyzed by PyMol software. For model stability studies, the three-dimensional (3D) PDB models were subjected to evaluation by Ramachandran plot analysis (Discovery Studio 4.5) . Based on the CAMP data set, SVM, random forest, and discriminant analysis algorithms were used to determine the possibility that the C-terminal α-helical peptide chain of the chimeric lysin is an antimicrobial peptide .…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As it is clear from the PROCHECK statistics of Ramachandran Plot (Table 1), a good quality model is expected to have over 90% in the most favoured regions [A, B, L] and the observed statistics show that the model has 92% residues in the favoured region possessing 303 residues out of 386 in favoured region. Therefore, on validating through statistics of Ramachandran plot (Figure 2) this model can be used as best model and used as target in docking studies [42]. End-residues (excl.…”
Section: Results and Discussion 31 In Silico Validation By Targeting Hbcatc In The Neuropathic Pains 311 Homology Modelingmentioning
confidence: 99%